Analisis Citra Pasar Bawah Sebagai Nukleus Pertumbuhan Kota Pekanbaru - Hariandi, Adek; Zulherman, Zulherman; Triana, Era (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
This research explores the role of Pasar Bawah as the nucleus of urban growth in Pekanbaru, focusing on identifying supportive and inhibiting factors affecting its development and formulating strategies to enhance its role in city development. A qualitative approach was employed, involving in-depth interviews with traders, visitors, and relevant stakeholders, alongside direct observations of market infrastructure and facilities. Findings reveal Pasar Bawah's pivotal roles as a local economic center, a shopping tourism attraction, a job creator, a stabilizer of the local economy, and a hub for social and cultural interactions. Supportive factors such as strategic location, diverse product availability, tradition, and government support contribute positively, while inadequate infrastructure, competition from modern markets, cleanliness and security issues, and lack of promotion pose significant challenges. Recommended strategies to augment Pasar Bawah's role include infrastructure revitalization, enhanced promotion and branding, collaboration with modern shopping centers, improved security and cleanliness measures, and empowerment of trader communities. This study aims to provide guidance for the development of traditional markets as integral components of sustainable and inclusive urban development.